(untitled) (City: History, Culture, Society, 2023)
A post-colonial approach to literary studies of modern literature, in particular Ukrainian, has gained considerable popularity over the last decade. Clearly, the collapse of the Soviet Union and the subsequent attainment of independence have laid the foundation for the development of post-colonial studies in our territory. Injuries inflicted during the long period of colonisation (although not all researchers agree to use this term, noting the absence of a key characteristic of the colony — “a large body of water” is missing) have been understood and reflected both in literature and its researchers. However, currently we are at a stage, when writers are moving beyond the refl ection typical for post-colonial viewpoints, delving into the exploration of logical connections between events and their consequences, examining ways to process these traumas. Therefore, in modern research, the decolonial approach, which emerges as a branch of postcolonial thought, is more relevant. In particular, this is discussed by Agnieszka Matusiak and Tamara Hundorova. Tamara Hundorova identifies a unique form of decolonial aesthetics in Ukrainian literature — aesthesis. This is the manifestation of the unknown, even the opposite of the generally accepted modern concept of “aesthetics” — corporeality, sensuality, and mystical practices. Agnieszka Matusiak observes that modern Ukrainian science and culture have undergone a ‘decolonial turn’ (decolonial-detotalitarian, as she calls this phenomenon, a complete shift in emphasis in discussions about Donbas). Decolonisation is intrinsically linked in Ukrainian realities with de-Sovietization. While at the governmental level, this occurs through changing street names and re-evaluating Soviet political figures, people raised under this system find it challenging to shed an identity formed under vastly different values and conditions. The article aims to showcase the depiction and transformation of the Soviet man in modern Ukrainian literature, illustrating changes that signify a shift towards a decolonial perspective. Also of interest are the aspects of traumatic memory and the identity crisis of characters, invariably linked with the disintegration of the Soviet Union.